Corporate Social Responsibility and Brand Equity: Moderating Effect of Consumer Trust in Emerging Market - Irawati, Intan; Mulyono, Sri; Sungkowati, Sri; Siagian, Ade Onny (International Journal of Business, Law, and Education, 2025)
Corporate Social Responsibility (CSR) has become a strategic priority for firms seeking to strengthen brand value, particularly in emerging markets where consumer expectations toward ethical and socially responsible business practices are rapidly evolving. This study investigates the influence of CSR on brand equity and examines the moderating role of consumer trust in enhancing this relationship. Utilizing a quantitative research approach, data were collected from 268 consumers in an emerging market context and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that CSR has a positive and significant effect on brand equity, demonstrating that responsible business initiatives contribute not only to social welfare but also to consumer perceptions of brand value. Moreover, consumer trust significantly moderates the relationship between CSR and brand equity, indicating that CSR initiatives are more effective when consumers perceive the brand as trustworthy. The study enriches stakeholder theory and consumer-based brand equity literature by emphasizing trust as a critical variable that reinforces CSR outcomes. Practical implications suggest that companies in emerging markets should design CSR programs aligned with consumer expectations while ensuring transparency and consistency to build stronger brand loyalty. Future research is encouraged to explore additional contextual factors and cross-industry comparisons for broader generalization.